2020
DOI: 10.3390/cancers12092407
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility to Endometrial Cancer: Risk Factors and Clinical Management

Abstract: Endometrial cancer (EC) is the most common cancer affecting the female reproductive organs in higher-income states. Apart from reproductive factors and excess weight, genetic predisposition is increasingly recognized as a major factor in endometrial cancer risk. Endometrial cancer is genetically heterogeneous: while a subgroup of patients belongs to cancer predisposition syndromes (most notably the Lynch Syndrome) with high to intermediate lifetime risks, there are also several common genomic polymorphisms con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 130 publications
1
34
0
3
Order By: Relevance
“…12 Mutations in cancer susceptibility genes (CSGs) other than those associated with LS are thought to play a smaller role in EC risk. 13 Although multigene panel testing (MGPT) studies performed for women with EC have identified PVs in other CSGs, [14][15][16] the true burden of PVs in other CSGs remains unknown. The modest number of cases investigated (381 in the study by Ring et al, 14 156 in Cadoo et al, 15 and 98 in Samadder et al 16 ), coupled with the fact that the cohorts overrepresent women with nonendometrioid, high-grade, and higher-stage tumors, limits our understanding of how frequent PVs in other CSGs are in the general EC population.…”
Section: Introductionmentioning
confidence: 99%
“…12 Mutations in cancer susceptibility genes (CSGs) other than those associated with LS are thought to play a smaller role in EC risk. 13 Although multigene panel testing (MGPT) studies performed for women with EC have identified PVs in other CSGs, [14][15][16] the true burden of PVs in other CSGs remains unknown. The modest number of cases investigated (381 in the study by Ring et al, 14 156 in Cadoo et al, 15 and 98 in Samadder et al 16 ), coupled with the fact that the cohorts overrepresent women with nonendometrioid, high-grade, and higher-stage tumors, limits our understanding of how frequent PVs in other CSGs are in the general EC population.…”
Section: Introductionmentioning
confidence: 99%
“…EC is genetically heterogeneous, apart from a patient’s subgroup belonging to a cancer predisposition syndrome, i.e., Lynch Syndrome, triggered by the germline alterations of DNA mismatch repair genes such as MLH1, PMS2, MSH2, and MSH6. EC also exhibits a high frequency of several other germline mutations in cancer predisposition genes [ 31 ].…”
Section: Incidence Of Female-oriented Cancersmentioning
confidence: 99%
“…Endometrial cancer (EC) is a malignant disease of the uterine inner layer (endometrium) developing from the glandular epithelium covering the luminal surface [ 1 , 2 , 3 ]. Most endometrial cancers are adenocarcinomas [ 3 ].…”
Section: Endometrial Cancermentioning
confidence: 99%
“…Potential risk factors for EC are well-known: obesity, insulin resistance, hypertension, nulliparity, early menarche, sedentary lifestyle, and anovulation contribute to the development of EC, especially in young patients [ 6 , 10 , 12 , 21 , 22 ]. EC is the most strongly hormone-dependent and excess-weight-related cancer [ 2 ]. These factors are linked to each other as elevated estrogen levels, especially those derived through the extragonadal estrogen aromatization pathway, are associated with increased body weight [ 2 , 4 , 6 , 21 ].…”
Section: Endometrial Cancermentioning
confidence: 99%